The Role of Educational Supervisors in Developing the Professional Performance of Social Studies Teachers in General Directorate of Education ,Baghdad ,Karkh II - Mhmood, Waleed Adnan (Journal of Tikrit University for Humanities, 2023)
The primary objective of the present research was to ascertain the specific role played by educational supervisors in enhancing the professional performance of social studies instructors within the directorate of education of Baghdad, Karkh II. In order to accomplish the study’s aims, the researcher devised questionnaires to assess the impact of educational supervisors on enhancing the professional performance of social studies instructors. The research population included 209 male and female instructors. A total of 230 questionnaires were collected and dispersed in a random manner. Out of these, 215 questionnaires were recovered, resulting in a retrieval rate of 93.4%. Following the auditing process, the researcher identified and excluded a total of 15 invalid questionnaires. Consequently, 209 questionnaires remained for analytical purposes. Subsequent to conducting statistical analysis, the researcher arrived at several findings, with the most significant being the moderate role of supervisors in enhancing the professional performance of social studies teachers within the Baghdad Al-Karkh II directorate.